Branching out: mobilizing community assets to support the mental health and wellbeing of children in primary schools - Dadswell, Anna; Bungay, Hilary; Acton, Faye; Walshe, Nicola (Frontiers in Public Health, 2024)
Introduction Mobilizing existing creative, cultural and community assets is seen as a crucial pathway to improving public health. Schools have been identified as key institutional community assets and arts-in-nature practice has been shown to promote children’s mental health. The ‘Branching Out’ research investigated how an established arts-in-nature practice called ‘Artscaping’ could be scaled up through the mobilization of community assets including school staff and local volunteers to reach more children in primary schools. Methods The Branching Out model was piloted in six primary schools across Cambridgeshire with ‘Community Artscapers’ delivering 1.5-h Artscaping sessions with children outdoors for 8 weeks. Interviews were conducted with 11 Community Artscapers (six school staff and five volunteers) and four school leaders reflecting on their experiences of the Branching Out model and the data was subject to a reflexive thematic analysis. Results The findings presented here discuss themes relating to mobilizing community assets, including framing the opportunity, recruiting and sustaining volunteers, training and supporting Community Artscapers, and tensions in roles and responsibilities. They also cover impacts for the children, including mental health provision, freedom in creativity and being outside, personal development, emotional impacts, and social connection, as well as impacts for the Community Artscapers, including making a difference, emotional wellbeing, personal and professional development, and connection and community. Discussion These findings are considered in terms of their alignment with public health policy drivers and the potential for the Branching Out model to become replicable and self-sustaining across schools to promote children’s mental health as a public health intervention.